Peripheral artery disease and physical function in women with and without HIV. (1st March 2022) - Cedarbaum, Emily R.; Ma, Yifei; Adimora, Adaora A.; Bamman, Marcas; Cohen, Mardge H.; Fischl, Margaret A.; Gustafson, Deborah; Matsushita, Kunihiro; Ofotokun, Igho; Plankey, Michael; Seaberg, Eric C.; Sharma, Anjali; et al.
Abstract : Objectives: Peripheral artery disease (PAD) is associated with decreased physical function and increased mortality in the general population. We previously found that PAD is common in middle-aged women with and without HIV infection, but its association with functional decline is unclear. We examine the contribution of PAD to functional decline in the Women's Interagency HIV Study, controlling for traditional cardiovascular risk factors and HIV-related factors. Methods: Analysis included 1839 participants (72% with HIV) with measured ankle–brachial index (ABI) and 4 m gait speed. ABI values categorized PAD severity. Linear models with repeated measures estimated the association of PAD severity with log-transformed gait speed after controlling for demographic, behavioral, and metabolic risk factors, and HIV/hepatitis C virus status. Results: Median age was 50 years and more than 70% were Black. Compared with normal ABI, there was a dose–response relationship between increasing PAD severity and slower gait speed in univariable analyses: 6% slower gait speed for low-normal ABI [95% confidence interval (CI): 4–9%], 10% for borderline PAD (95% CI: 6–13%), 14% for mild PAD (95% CI: 9–18%), and 16% for moderate–severe PAD (95% CI: 5–25%). PAD severity remained associated with slower gait speed in multivariable analyses. HIV/hepatitis C virus co-infection was independently associated with 9% (95% CI: 4–14%) slower gait speed compared with those with neither infection. Among women with HIV, neither CD4 + cell count nor HIV-RNA level was associated with gait speed. Conclusion: In middle-aged women with and without HIV infection, greater PAD severity is associated with progressively slower gait speed. Early detection of subclinical PAD may decrease the risk of lower extremity functional impairment and its long-term health consequences.